Optimization of biosurfactant production by Pseudomonas aeruginosa 44T1 - M. Robert; E. Mercadé; C. Andrés; M. J. Espuny; M. A. Manresa; J. Guinea (Grasas y Aceites, 1991)
This work describes the experimental results carried out on the optimization of the fermentation media of Pseudomonas aeruginosa 44T1 which produces surface active products when grown on glucose as carbon source. Several parameters of the media have been found to be critical for the production of biosurfactants by this strain. The C/N ratio, the iron concentration and the incubation temperature cause a high increase of the CMC-1 values as a measure of surfactant production.